2013
DOI: 10.1108/et-02-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

A critical account of practice within an innovative Foundation degree in UK higher education

Abstract: Purpose -The purpose of this paper is to explore the views of academics, senior university managers and employer representatives on the design and implementation of an innovative work-based learning (WBL) programme in UK higher education. Design/methodology/approach -The research project draws upon case study research and utilizes data from semi-structured interviews and documentary analysis of policy papers. The experiences of university staff and employer representatives were analysed methodologically using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…One is related to capabilities available in the school domain. Studies by Costa (2009); Smith et al (2013) and Xia et al (2015) clearly emphasize the need for sufficient programme support particularly in the school domain to enable students to enter the host-firm and to enable the host-firm to handle inexperienced students. Other studies found that successful industry-university collaborative partnerships involved engagement such as having qualified WIL contactable staff in schools and businesses .…”
Section: Lack Of Institutional Support (Is)mentioning
confidence: 99%
See 2 more Smart Citations
“…One is related to capabilities available in the school domain. Studies by Costa (2009); Smith et al (2013) and Xia et al (2015) clearly emphasize the need for sufficient programme support particularly in the school domain to enable students to enter the host-firm and to enable the host-firm to handle inexperienced students. Other studies found that successful industry-university collaborative partnerships involved engagement such as having qualified WIL contactable staff in schools and businesses .…”
Section: Lack Of Institutional Support (Is)mentioning
confidence: 99%
“…Pavlin (2016) suggest that WIL stakeholder motivational differences are compounded by institutional value differences. Smith et al (2013) emphasizes these value differences embracing attitudes and ability to build long-term commitment based on a true understanding and acknowledgement of host-firm needs. Nikolova and Andersen (2017) points out that understanding the client needs and mechanisms to support outcomes for the host was imperative in order to enable student learning in the host-firm domain.…”
Section: Lack Of Institutional Support (Is)mentioning
confidence: 99%
See 1 more Smart Citation